PENGARUH KREDIBILITAS PUBLIC RELATIONS TERHADAP NIAT BERINVESTASI PASAR MODAL YANG DIMEDIASI OLEH SIKAP CALON INVESTOR - Chandra, Yohan Hardy; Aksari, Ni Made Asti (E-Jurnal Manajemen, 2017)
This study aimed to determine the effect of public relations credibility on the intention to invest in the capital market, mediated by the attitude of potential investors. This research was conducted in the Indonesia Stock Exchange at their Denpasar Representative Office, an institution authorised to regulate and supervise the activities of the capital market investment in Bali. The number of respondents in this study is 140 which was determined by purposive sampling method, and data were collected through questionnaires. This study used path analysis to search for causal relationships between variables. The result of this study indicates that, as a mediator, potential investors attitude have a positive and significant effect on the influence of public relations credibility towards intention to invest in the capital market in Bali. Indonesia Stock Exchange Denpasar Representative Office is expected to constantly improve their competence in providing understanding to potential investors about the benefits of capital marketinvestment through various capital market education activities.
Keywords: credibility; public relations; atitudes; intentions to invest; capital markets